Efecto de la inoculación de bacterias promotoras de crecimiento vegetal en pasto Ryegrass perenne sometido a déficit hídrico (2020)
Perennial ryegrass is a forage commonly used in template regions of Colombia for livestock feeding. It has high nutritional values but needs large amounts of water to achieve an optimal growth. The aim of this work was to determine if the inoculation of plant growth-promoting bacteria (PGPB), individually or in dual inoculations, can help to improve the response of this grass to water deficit. First, an assay was performed to select the PGPB that could influence biomass production under 10 days of water deficit. Three co-inoculations were selected: 1) Herbaspirillum sp. AP02 and Herbaspirillum sp. AP21; 2) Herbaspirillum sp AP02. and Pseudomonas sp. N7; and 3) Herbaspirillum sp. AP21 and Azospirillum sp. D7. In vitro assays suggested that these bacteria can colonize ryegrass internal tissues and improve seedlings growth under simulated water deficit (p<0.05). Plant growth-promoting activities evaluation showed an increase in indolic compounds for some dual inoculations, and a negative effect in exopolysaccharide production (p<0.05). Finally, a greenhouse experiment was performed to test the ability of these bacteria to modify some physiological, biochemical and morphological traits of this grass under water deficit. The bacteria had an effect in shoot biomass production, stomatal conductance, proline accumulation and chlorophyll pigments during the days of water deficit (p<0.05). They also improved leaves water status after rehydration, about 12% higher than the control. These results might be the first step to find a PGPB consortium that can help improve the response of ryegrass pastures to water deficit.